2015
DOI: 10.7314/apjcp.2015.16.11.4745
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Circulating Tumor Cells (CTCs) but not Primary CTCs are Associated with the Clinico-Pathological Parameters in Chilean Patients With Colo-Rectal Cancer

Abstract: Background: The aim of this study was to assess detection of circulating tumor cells (CTC) using anti-CEA pre and post surgery in Chilean patients with colo-rectal cancer. Materials and Methods: The presence of CTCs was evaluated in 80 colorectal cancer patients pre and post surgery using standard immunocytochemistry and the results were compared with findings for standard clinico-pathological parameters. Results: In patients presurgery CEA (+) CTCs were frequently found, with no relation to tumor size or noda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…CTCs change from being positive to negative in 27%–51% of patients in some studies [17,18]. For bone marrow micro‐metastasis, another study reported 26% of patients changed from positive to negative after curative surgery [19]. Although sampling errors may be the cause of these differences, this article questions whether improved immune function after primary tumour results in an increase in MRD‐negative disease with the elimination of CTCs and micro‐metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…CTCs change from being positive to negative in 27%–51% of patients in some studies [17,18]. For bone marrow micro‐metastasis, another study reported 26% of patients changed from positive to negative after curative surgery [19]. Although sampling errors may be the cause of these differences, this article questions whether improved immune function after primary tumour results in an increase in MRD‐negative disease with the elimination of CTCs and micro‐metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This feature can aid in the selection of appropriate treatments and provide an extraordinary prognostic marker [9]. For example, in a recent study of colorectal cancer, CTCs originating from metastases, defined as nucleated cells expressing CEA (a set of highly related glycoproteins involved in cell adhesion), but not CD45, were shown to be associated with increased risk of relapse [10]. However the presence of primary CTCs did not have the same strong predictive value.…”
Section: Liquid Biopsy: Technologies Advancing Personalized Medicinementioning
confidence: 99%
“…Generally, the filtration system consists of a filtration tube containing the membrane, a manifold vacuum plate with valve settings, a vacuum manifold and a vacuum pump [109][110][111]. Following filtration, CTCs can be stained by standard immuhistochemistry techniques to identify specific proteins or nucleic acid can be extracted and analyzed by ddPCR or NGS to identify mutations [107,[112][113][114]. Oh and coworkers used a high-density microporous chip filter to enrich CTCs and evaluate its clinical utility in colorectal cancer.…”
Section: Methods To Isolate and Identify Ctcmentioning
confidence: 99%